Glycosilation reaction models and the role of Madagascar periwinkle (Catharanthus roseus CU G. Don)' S leaves infusion as protein damage inhibitor - Rizky Taufan Firdaus Rizky Taufan Firdaus (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background : Glycosilation is a reaction between protein and glucose in high concentration. The basic of this reaction is the continuous increase of glucose concentration, followed by a hooking between glucose with the amin primary structure of the protein. Beside form the AGEs, glycosilation reaction forms free radicals as the side product. The free radical reaction with the protein forms a crosslinking of the protein and then change the structure of the protein.Objectives : This research was carried out to know glycosilation reaction model and the role of madagascar periwinkle ICatharanthus roseus ELI G. Don)' s leaves infusion as protein damage inhibitor. Method : This research is an experimental and explorative research. This research was carried out in two steps, the making of infusion and the test for protein damage inhibition by using the infusion of madagascar periwinkle' s leaves and glyclazide.Result : The activity of madagascar periwinkle's leaves infusion to inhibit the protein damage is 21,29% while the activity of glyclazide is 96,77%.Conclusion : The infusion of madagascar periwinkle (Caiharanihus roseus EL.] G. Don)'s leaves can inhibit the protein damage because of the glycosilation reaction but lower than the glyclazide's.Key words : Madagascar periwinkle - glycosilation - free radical - protein damage